FRI0366 From Symptom Onset to Effective Early Rheumatoid Arthritis Care: The General Practitioners' Perspective. (9th June 2015) - Meyfroidt, S.; Stevens, J.; De Lepeleire, J.; Westhovens, R.; De Cock, D.; Van der Elst, K.; Vanhaecht, K.; Verschueren, P.
Abstract : Background: General practitioners (GPs) play a crucial role in the management of early rheumatoid arthritis (ERA), a disease affecting 0.8% of the population worldwide. The experiences, beliefs and attitudes of GPs with regards to the management of ERA remain unknown. Objectives: To explore GPs' experiences, beliefs and attitudes regarding ERA detection, referral and initial intensive treatment use. Methods: A qualitative study was conducted using individual, in-depth, face-to-face interviews with 13 GPs. Interviews were audio-recorded, transcribed verbatim and coded using the constant comparative method. Results: GPs applied many different examination techniques for ERA detection and prescribed regularly non-steroidal anti-inflammatory drugs if they suspected ERA. However, GPs felt unconfident in the detection due to symptoms of ERA often being insufficiently clear, inconclusive results of diagnostic tests and low incidence of ERA in the general practice. GPs mentioned various approaches and multiple factors determining their referral decision. Perceived referral barriers included limited access to rheumatology services and long waiting lists. GPs considered intensive treatment initiation as belonging to the expertise of rheumatologists. GP-reported key barriers to intensive treatment included patients' resistance and non-adherence, lack of GP involvement and unsatisfactory collaboration with rheumatology services. Conclusions: GPs recognised the importance of rapid detection and initial intensive treatment for ERA, but experienced various related barriers. ERA management in general practice could be improved by targeting GPs' skills to detect ERA, better collaboration with rheumatology services and developing an ERA care pathway. Acknowledgements: The authors thank the GPs who participated in this study for their time and openness during the interviews. Disclosure of Interest: None declared